La planificación microcurricular y su incidencia en la estimulación de las funciones sensoriales de los niños de primer año de educación básica de la Unidad Educativa Fiscomisional La Inmaculada del cantón Zamora, período 2009-2010. Lineamientos alternativos - Lapo Calva, Janneth Emperatriz (2011)
The present titled investigative work, "The planning microcurricular and their incidence in the stimulation of the sensorial functions of the children of the first year of Basic Education of the Educational Unit Fiscomisional the Immaculate of the Canton Zamora, period 2009-2010. Alternative limits", he/she had like investigated sample a total of 77 children the same one that approached the incidence of the planning microcurricular in the stimulation of their sensorial functions, being these affected by the limited employment of methodological strategies used by the teachers. The desire that the present investigation is good to obtain the Master in Infantile Education and consequently the professional superación; this way this work was centered in activities like: I study bibliographical, field observation, surveys to family parents, teachers, he/she interviews the Hna. Directress of the mentioned educational institution. Detected the problematic field and to carry out the investigated work they thought about the following objectives: general objective had as purpose to determine the incidence that has the planning microcurricular in the stimulation of the sensorial functions of the first year-old children. He/she also intended to reach the following specific objectives: to know the incidence of the planning microcurricular in the development of the sensorial functions of the children of first year of Basic Education of the Educational Unit Fiscomisional The Immaculate of Zamora's city. To evidence if the methodological strategies of the planning microcurricular influence in the stimulation of the sensorial functions of the first year-old children. The hypotheses that guided the present work, establish the planning microcurricular and the methodological strategies used by the teachers they don't contribute in their entirety to the stimulation of the sensorial functions of the children of the first year of Basic Education of the Educational Unit Fiscomisional The Immaculate of Zamora's city, the scarce planning microcurricular impacts in the development of the sensorial functions of the first year-old children and the limited employment of methodological strategies that the teachers use it influences in the stimulation of the sensorial functions of the first year-old children, the same ones that are proven being based in the investigation through the information obtained by means of the application of the established instruments for its realization. After an analysis and discussion of results of the present investigative work, it has been possible to reach the following conclusions, the same ones that remark: 1. he/she has been able to verify that 67% of the teachers don’t take a planning microcurricular, generating a considerable percentage of children that you/they present difficulties in its auditory, visual and tactile perceptions. 2. The methodological strategies that more the teachers use they are: the game directed in 33%, I play symbolic in 17% and shops in 33%, allowing the stimulation of the boy's sensorial functions and consequently the access to the logical, creative, critical thought and the social world. 3. The family parents consider that it is necessary to implement methodological strategies that allow the development of the sensorial functions of their children. Culminated the present investigation work thinks about the following recommendations that have as end the one of offering a positive contribution focused to the importance that has the planning microcurricular in the stimulation of the sensorial functions of the first year-old children. 1. To suggest the organization of seminars, directed to the first year-old teachers, with the purpose of making aware the importance of the planning microcurricular in the stimulation of the sensorial functions of the investigated children. 2. To the teachers of the first years of basic education so that they apply methodological strategies in a planned way, considering the necessities of their students, with the purpose of providing the objectives that love each other to achieve, accurately and this way to reach good learning in the children. 2. Permanent training to the teachers in the courses of upgrade and curricular invigoration that it offers the Ministry of Education with the purpose of improving their educational practice. Therefore an alternative proposal was elaborated so that it facilitates to the educated ones infantile a better handling of methodological strategies that you/they contribute to the development of the sensorial functions of the children of the Educational Unit Fiscomisional the Immaculate one.